INFLUENCE OF PALM METHYL ESTER (PME) AS AN ALTERNATIVE FUEL IN MULTICYLINDER DIESEL ENGINE - Mohd Hafizil M. Yasin; R. Mamat; K.V. Sharma; Ahmad Fitri Yusop (Journal of Mechanical Engineering and Sciences, 2012)
Palm oil is one of the vegetable oil, which is converted to biodiesel through a transesterification process using methanol as the catalyst. Palm oil biodiesel or palm methyl ester (PME) can be used in diesel engines without any modification, and can be blended with conventional diesel to produce different proportions of PME-diesel blend fuels. The physical properties of PME were evaluated experimentally and theoretically. The effect of using neat PME as fuel on engine performance and emissions was evaluated using a commercial four-cylinder four-stroke IDI diesel engine. The experimental results on an engine operated with PME exhibited higher brake specific fuel consumption in comparison with the conventional fuel. With respect to the in-cylinder pressure and heat release rate, these increased features by over 8.11% and 9.3% with PME compared to conventional diesel. The overall results show that PME surpassed the diesel combustion quality due to its psychochemical properties and higher oxygen content.